Multivariable model development and internal validation for prostate cancer specific survival and overall survival after whole-gland salvage Iodine-125 prostate brachytherapy. Issue 1 (April 2016) - Peters, Max; van der Voort van Zyp, Jochem R.N.; Moerland, Marinus A.; Hoekstra, Carel J.; van de Pol, Sandrine; Westendorp, Hendrik; Maenhout, Metha; Kattevilder, Rob; Verkooijen, Helena M.; van Rossum, Peter S.N.; Ahmed, Hashim U.; Shah, Taimur T.; et al.
Abstract: Background: Whole-gland salvage Iodine-125-brachytherapy is a potentially curative treatment strategy for localised prostate cancer (PCa) recurrences after radiotherapy. Prognostic factors influencing PCa-specific and overall survival (PCaSS & OS) are not known. The objective of this study was to develop a multivariable, internally validated prognostic model for survival after whole-gland salvage I-125-brachytherapy. Materials and methods: Whole-gland salvage I-125-brachytherapy patients treated in the Netherlands from 1993-2010 were included. Eligible patients had a transrectal ultrasound-guided biopsy-confirmed localised recurrence after biochemical failure (clinical judgement, ASTRO or Phoenix-definition). Recurrences were assessed clinically and with CT and/or MRI. Metastases were excluded using CT/MRI and technetium-99m scintigraphy. Multivariable Cox-regression was used to assess the predictive value of clinical characteristics in relation to PCa-specific and overall mortality. PCa-specific mortality was defined as patients dying with distant metastases present. Missing data were handled using multiple imputation (20 imputed sets). Internal validation was performed and the C-statistic calculated. Calibration plots were created to visually assess the goodness-of-fit of the final model. Optimism-corrected survival proportions were calculated. All analyses were performed according to the TRIPOD statement. Results: Median total follow-up was 78 months (range 5–139). A total of 62 patients were treated, of which 28 (45%) died from PCa after mean (±SD) 82 (±36) months. Overall, 36 patients (58%) patients died after mean 84 (±40) months. PSA doubling time (PSADT) remained a predictive factor for both types of mortality (PCa-specific and overall): corrected hazard ratio's (HR's) 0.92 (95% CI: 0.86–0.98, p = 0.02) and 0.94 (95% CI: 0.90–0.99, p = 0.01), respectively (C-statistics 0.71 and 0.69, respectively). Calibration was accurate up to 96 month follow-up. Over 80% of patients can survive 8 years if PSADT > 24 months (PCaSS) and >33 months (OS). Only approximately 50% survival is achieved with a PSADT of 12 months. Conclusion: A PSADT of respectively >24 months and >33 months can result in >80% probability of PCa- specific and overall survival 8 years after whole-gland salvage I-125-brachytherapy. Survival should be weighed against toxicity from a salvage procedure. Larger series and external validation are necessary.